Answer:
Option B gives the directly proportional relation.
Step-by-step explanation:
If a function can be written as in the form y = kx ........... (1), where x is the independent variable, y is the dependent variable and k is the proportionality constant.
Now, from the given four tables in options, the table in option B only satisfies this relation between x and y.
The ordered pairs in the option B are (1,0.5), (2,1), (3,1.5) and (4,2).
Now, take any two pairs of coordinates and find the equation of the function that satisfies all four points.
Taking (1,0.5) and (2,1) points, the equation of the straight line will be
⇒ 2(y - 1) = x - 2
⇒ 2y = x
⇒
............. (2)
Therefore, this equation (2) is similar to equation (1) and hence this table is directly proportional relationship. (Answer)
Answer:
d= 10.44030651
Step-by-step explanation:
The diameter is the length between the endpoints. We can find it using the distance formula.
d= sqrt((x2-x1)^2+(y2-y1)^2 )
d = sqrt((-6-4)^2+ (-1-2)^2)
d = sqrt((-10)^2+(-3)^2)
d= sqrt(100+9)
d = sqrt(109)
d= 10.44030651
Answer:
Step-by-step explanation:
<u>Statements </u> <u> Reasons</u>
1) QS =42 Given
2) QR + RS = QS Segment Addition Postulate
3) (x + 3) + 2x = 42 Substitution Property
4) 3x + 3 = 42 Simplify
5) 3x = 39 Subtraction Property of Equality
6) x=13 Division Property of Equality
Explanation:
We have given QS=42. We have to prove that x=13
We will use Segment Addition Postulate which states that given 2 points Q and S, a third point R lies on the line segment QS if and only if the distances between the points satisfy the equation QR + RS = QS.
Then we will substitute the values in the defined postulate.
where QR= x+3
RS=2x
QS=42
QR+RS=QS
(x+3)+2x= 42
Now simplify the expression by opening the brackets.
x+3+2x=42
3x+3=42
Now subtract 3 from both sides.
3x+3-3=42-3
3x=39
divide both sides by 3.
3x/3 =39/3
x=13..
When u add it stays the same but for subtraction u change the sign.
Example: 2- (-5)=7
9514 1404 393
Answer:
False
Step-by-step explanation:
The given formula is the "explicit" formula for the sequence.
The recursive formula would be ...
a[1] = 160
a[n] = 1/2·a[n-1] . . . . each term expressed in as a function of previous terms
The given statement is false.